Peran Tata Usaha dalam Pengelolaan Aset Barang Milik Sekolah di SMAN 3 Takalar - Nasir, Nasir (Universitas Methodist Indonesia, 2025)
The management of school-owned assets is an important part of education management which aims to support the effectiveness of the learning process. Administration as an administrative implementer has a strategic role in ensuring that school assets are properly recorded, monitored, and reported. This study aims to describe the role of administration in asset management at SMAN 3 Takalar and identify the obstacles faced in its implementation. This research uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The research subjects consist of administrative staff, principals, and teachers. The results of the study show that administrative staff have carried out asset management tasks such as recording, labeling, and reporting assets on a regular basis. However, the administrative process is still mostly done manually and has not been fully supported by the digital system. The main obstacles found are the lack of technical training for staff and the lack of optimal coordination between departments in asset reporting. However, there is a fairly good procedural awareness in the implementation of tasks. This study recommends the need for continuous training for administration, the implementation of digital-based asset information systems, and increased collaboration between the administration and all school residents to create more effective and accountable asset management.